2000
DOI: 10.1042/bj3450603
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolic changes caused by short-chain ceramides and the connection with apoptosis

Abstract: The effects of the short-chain ceramides D-erythro-N-acetylsphingosine (C2-ceramide), 6-[N-(7-nitrobenz-2-oxa-1,3-diazole-4-yl)amino]hexanoyl-D-erythro-sphingosine (NBD-ceramide) and N-[4,4-difluoro-5,7-dimethyl-4-bora-3a,4a-diaza-s-indacene-3-pentanoyl]-D-erythro-sphingosine (DMB-ceramide) on the incorporation of [14C]acetate into baby-hamster kidney (BHK) fibroblasts have been examined. C2-ceramide at concentrations up to 20 μM caused an inhibition of synthesis of phosphatidylcholine (PtdCho), sphingolipids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies reported the apoptotic effect of permeable unnatural short-chain ceramides on cells. 30,31 However, short-chain ceramide analogues differ significantly in their physical membrane properties as well as biological activity compared to natural long-chain ceramides. 32,33 Therefore, these short-chain analogues are limited in their use in structure−function analyses relevant to natural ceramides and do not enable direct studies on how the structure of the N-acyl group of ceramides affects apoptosis.…”
Section: ■ Chemoselective Synthesis Of Sphingolipids In Living Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported the apoptotic effect of permeable unnatural short-chain ceramides on cells. 30,31 However, short-chain ceramide analogues differ significantly in their physical membrane properties as well as biological activity compared to natural long-chain ceramides. 32,33 Therefore, these short-chain analogues are limited in their use in structure−function analyses relevant to natural ceramides and do not enable direct studies on how the structure of the N-acyl group of ceramides affects apoptosis.…”
Section: ■ Chemoselective Synthesis Of Sphingolipids In Living Cellsmentioning
confidence: 99%
“…Our initial experiments enabled us to directly detect the apoptotic effect of saturated long-chain ceramides within cells using in situ lipid synthesis, confirming previous conclusions that were made indirectly by using short-chain ceramides. 30 However, the effect of N-acyl chain length or saturation on ceramide function had not been directly investigated in previous studies. Human cells produce a number of different ceramide species that differ in N-acyl chain length.…”
Section: ■ Chemoselective Synthesis Of Sphingolipids In Living Cellsmentioning
confidence: 99%
See 1 more Smart Citation